Pengaruh Penerapan Pemidanaan di Undang-Undang Cipta Kerja Bagi Pemulihan Lingkungan Hidup - Yulianto Bayu Setiyawan; Aullia Vivi Yulianingrum (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This research is to find out the effect of Law No. 11 of 2020 concerning Job Creation on environmental restoration and the influence of crime on the environment. This research uses a normative juridical type of research, legal research uses library research. The basis of this research is the reduction of regulations on protection for the environment, especially in the field of utilization of natural resources in the East Kalimantan region, this can be seen from the issuance of the Job Creation Law which trimmed/replaced regulations from the previous law which was considered to suppress the previous regulations so that it became a threat of arrest. uncontrollable environmental damage. Basically regulations or rules are used to give rules to the public so they don't act as they please, that everything in a country has rules with criminal penalties that aim to give fear to the public so they don't violate existing rules. The drafting of regulations for Law No. 11 of 20 Concerning Job Creation was driven with the aim of improving the economic and labor aspects of simplifying the EIA in the Job Creation Law to make it easier for entrepreneurs to arrange permits for the utilization of natural resources in the coal mining sector so that many investors are willing to investing in and working with coal mining entrepreneurs also adds to jobs because many entrepreneurs carry out mining activities and of course the economy increases in an area, but behind all that there is a threat of great environmental damage that will befall something if there are no rules that are able to provide protection against environment that has been destroyed as a result of arbitrary human actions, this is the view of the government in making laws and regulations so that it does not only prioritize economic value but also pays attention to what impacts occur as a result of taking natural resources so that a balance must be made so that environmental damage can be overcome.